Field notes and letter to Thomas H. Kent contributed by Michael Overton, October 19, 1998 - Overton, Michael D.et al (1998)
Fall report of birds found in central Iowa contributed by Michael Overton. Also included is a letter from Overton to Thomas H. Kent regarding the early submission date of the fall bird sightings. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of fall 1998. Epson - sheet feed